Measuring Influencing Remittance Sending by Indonesian Migrant Workers - Widyawati, Retno Febriyastuti; Andi Lopa Ginting (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study aims to determine the effect of income, work experience, gender, and age of Indonesian Migrant Workers on remittances in ten districts/cities in East Java Province. This study uses primary data obtained from interviews. The analysis technique uses multiple linear regression analysis using EViews 12 software. The study results indicate that the income variable positively and significantly affects remittances sent by Indonesian Migrant Workers in ten districts/cities in East Java Province. Meanwhile, for the work experience variable, gender and age of Indonesian Migrant Workers have a negative and insignificant effect on remittances in ten districts/cities in East Java Province. The allocation of remittances is used for productive activities such as to meet daily needs and education costs. There are also investment activities such as buying land, buying livestock, and saving in banks. In addition, remittances sent by Indonesian Migrant Workers are used to pay debts. This study contributes to understanding the dynamics of remittances in East Java and can be a basis for formulating policies that support the welfare of migrant workers and their families. Keywords: Remittance; Income: Work Experience; Gender; Age